The Role of Value-Semantic Oppositions in Revealing the Deep Literary and Psychological Characteristics of the Narrator’s Image in “Poor Liza” by N.M. Karamzin - Krasnova, Olga (Philology & Human, 2021)
Value-semantic oppositions in the novel by N.M. Karamzin, seen as meaningful text dominants in situations of "existential fullness", are discussed in the article from the point of view of an interdisciplinary approach of literary criticism, text theory, psychology and linguistics. The article describes the process of literary and psychological meaning generation, coupled with the narrator’s inherent properties, as well as implicit literary and psychological textual relationships with inherent properties, it also singles out the contextual ways of these characteristics, reflecting motives, attitudes, generalized worldview judgments (generalizations). The author shows the dialog nature of the narrator’s literary and psychological attitude to the realities denoted by various parts of the opposition in the situation of “existential fullness”. The role of lexical markers corresponding to the depicted integral emotional state of the narrator in the privision of active reader’s attention and attracting him to the deep literary and psychological characteristics is revealed.